Three species of Colletotrichum are associated with anthracnose of pomegranate in Brazil - Silva-Cabral, Janaíne Rossane Araújo; Batista, Lourdes Regina Lopes; Costa, Jaqueline Figueredo de Oliveira; Amorim, Edna Peixoto da Rocha; Lima, Gaus Silvestre de Andrade; Assunção, Iraildes Pereira (Comunicata Scientiae, 2020)
Pomegranate is a fruit rich in vitamins and secondary metabolites used in traditional medicine and industry. However, production losses have been associated the anthracnose, disease caused by Colletotrichum species. This is an important disease of the pomegranate, as it affects the yield and the quality of the fruits. The present study aimed to investigate which species of Colletotrichum are associated with anthracnose disease in pomegranate in the Northeast region of Brazil, using multi-locus phylogenetic analysis and morpho-cultural characteristics. The total DNA extracted was amplified with GAPDH, TUB2, CAL, ACT genes and the ITS-rDNA region. The sequences obtained were used for the construction of phylogenetic trees of Bayesian inference. The mycelial growth rate, size and shape of the conidia and appressories were evaluated for the morpho-cultural characterization of the species. Six isolates were analysis and three species belonging to the C. gloeosporioides complex were identified in this study. This is the first report of C. theobromicola (2) in pomegranate fruit in Brazil and C. siamense (2) and C. fructicola (2) in the world.